Investigation of fatty acid composition and trans fatty acid formation in extracted oils from French-fried potatoes and classification of samples using chemometric approaches - Yildirim, Elif; Toker, Omer Said; Karaman, Safa; Kayacier, Ahmed; Dogan, Mahmut (Tubitak Scientific & Technological Research Council Turkey, 2015)
The present study investigates fatty acid composition and trans fatty acid formation in oils extracted from French-fried potatoes, which were produced in the laboratory and collected from different restaurants. Potatoes were fried at 180 degrees C at different frying periods (1, 7, 13, 19, 25, and 31 min) and the fatty acid composition of the extracted oils was determined. Principal component analysis and hierarchical cluster analysis were used to characterize and classify the samples. Four major fatty acids were identified in the samples, namely palmitic acid, stearic acid, oleic acid, and linoleic acid. Linolelaidic acid (C18:2 trans) was detected in the oil samples extracted from potatoes fried in margarine. Three principal components (PCs) and 4 main clusters were obtained from the chemometric analysis, which characterized the samples. Three PCs were found to be explanatory of more than 84.96% of the total variability in the data set.
Keywords: Fatty acid composition; French-fried potatoes; trans configuration; principal component analysis; hierarchical cluster analysis; VEGETABLE-OILS; PRINCIPAL-COMPONENT; MARGARINES; PROFILE; Agriculture; Forestry